Empowerment of beekeepers Trigona Sp. in Buahan Village based on the concept of 'The Spirit of Sobean' - Ni Kadek Ajeng Wangi; Bhuanaputri Bhuanaputri; Felicia Johnny Alberta; I Gede Krisna Yoga Putra Pratama; Made Mutiari Putri Udayani; Ni Made Ayu Natih Widhiarini; I Wayan Eka Mahendra (Universitas Muhammadiyah Magelang, 2021)
Buahan Village is a village located in Payangan District, Gianyar Regency which has the potential to be developed in the agricultural and plantation sectors. Among them is the increased production of honey and processed honey in the form of herbal drinks, which greatly affect the income of MSMEs Buahan Mesari and Amerta Herbal. The problem faced is the lack of knowledge of MSMEs in Buahan Mesari regarding techniques for cultivating Trigona sp. bees. and the lack of insight into Amerta Herbal SMEs in developing efficacious herbal beverage derivative products. Through training for the people of Buahan Village related to Trigona sp. bee cultivation and the manufacture of kele honey-based products that are able to generate increased income and community welfare caused by increased product sales in the midst of the Covid-19 pandemic.